# How do you solve the following system?: #4x-y=-1 , 6x - 4y = 3 #

##### 1 Answer

#### Answer:

Use the elimination method.

Your answer is:

x =

y =

#### Explanation:

I'd say for this one, I would use the elimination method. I'm not too good at formatting, but I'll give this my best shot.

Set it up like this:

4x - y = -1

6x - 4y= 3

Now, you want to get rid of one of the variables. Multiply (4x-y=-1) by -4. Now you have:

-16x + 4y = 4

6x - 4y = 3

Cancel out the 4y and -4y and add the rest of the similar terms. You're left with

-10x = 7

Divide both sides by -10 so you have just x.

x =

Now, plug x back into one of the equations. You can do either, but for this one I'll do the first one.

4(

4(

So...

Move the

-y =

Divide both sides by -1.

y =

Your answer is:

x =

y =